Personal and social drivers of eco-halal consumption: The role in ensuring halal industry sustainability - Sholihah, Erlinda; Ariyani, Diyah; Zaenuri, Ahmad; Ulwiyyah, Ulwiyyah (International Journal of Halal Industry, 2025)
Purpose – Based on Stimulus–Organism–Response (SOR) theory, this study investigates how the S-O-R model influences eco-halal consumption, which contributes to halal industry sustainability. Methodology – A quantitative survey design was used with 207 eco-halal consumers in Central Java, Indonesia, selected through purposive sampling. Data were collected through online questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Findings – The results revealed that religiosity, health consciousness, eco-halal literacy, lifestyle, and social influence significantly and positively shaped eco-halal consumption, whereas price did not have a significant effect. Furthermore, eco-halal consumption strongly and positively influences halal industry sustainability. Implications – Theoretically, this study enriches the eco-halal consumer behavior literature by highlighting the dominance of spiritual, ethical, and sustainability-oriented factors. Practically, it provides insights for halal industry stakeholders to improve competitiveness through eco-friendly, ethical, and health-conscious practices aligned with consumer expectations. Originality – This study is among the first to empirically link eco-halal consumption with halal industry sustainability in Indonesia. It emphasizes the integration of religiosity, health consciousness, and eco-halal literacy as the key drivers of the sustainable halal industry